(3UMjM eSdes - (3GdbTjQj GdfjSGHhQqi, CHh GdMSjf, eSde Hf GdMLGL Hf eSde, J (B261 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; CNHQfG GdTjN GdTQja GdRGgO GdfbjH GdKbI CHh GdYHGS CMeO Hf eMeO Hf YHO GdYRjR GdYHGS Gdecj bQGAI Ydjg aCbQ Hg bGd (B( (3CfG (B) (3GdTjN Gdabjg CHh Ydj GdMSjf Hf Ydj GdWHQj bQGAI Ydjg aj efRdg HecI MQSgG Gddg hCfG CSeY hgh jSeY aCbQ Hg hbGd fYe hPdc aj TgQ TfI KdGKI hJSYjf hCQHYeGFgs
(3BNQgG (B:s
(3bGd MOKfG ESeGYjd Hf EHQGgje CNHQfG OGhO Yf GdTYHj Yf LQjQ Hf YHO Gddg bGd (B: (3bGd QShd Gddg Udi Gddg Ydjg hSde (B: " (3EPG GJGce GdeUOb adjUOQ efce hgh Yfce QGV (B" (3Je GdLRA GdChd ef UMjM eSde jJdhg GdLRA GdKGfj cJGH GdUhes
(3fSNJ HCeQ (B: (3YR GdOjf Hf eMeO Hf YR GdOjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 221s
(3eYLe GdeDdajf (B3 / 851s
(3cTa GdXfhf (B1 / 555s
(3TPQGJ GdPgH (B2 / 144s
Keywords: (3GdMOjK hGdeUWdMs